Project for recycle bubble wrap, used plastic and patchwork into sitting pillows: Environmental education efforts - Siti Roudlotul Hikamah; Riza Rullah; Devi Nurkholisoh; Tubagus Sholihin; H. Hariyanto (University of Muhammadiyah Malang, 2024)
Waste, a byproduct of human activity, can cause environmental pollution if released without proper processing. It can accumulate in piles, disturbing natural beauty and emitting unpleasant odors. The aim of this research is to from the students to care about the environment by learning with the Bubble Wrap Recycling Project, Used Plastic and Patchwork. The method of this project is a structured experiment. Common waste includes bubble wrap, plastic, and rags from the convection industry. A student project in an environmental science course involved recycling these materials into sitting pillows. Three variants were tested: 10% bubble wrap, 10% plastic waste, 80% patchwork, 15% bubble wrap, 15% plastic waste, 70% rags, and 20% bubble wrap, 20% plastic waste, 60% rags. The pillow's comfort was measured using a Linkert scale of 1-5. The results showed that the pillow measures 40cm. Recycling is a way to promote environmental care and awareness. Cooperation from educational agents, such as supervisors, leaders, and lecturers, is needed to increase students' environmental awareness. This includes examples of good environmental actions in daily routines, such as disposing of waste and implementing 3R practices.